Brands for A Cause: The Effect of Cause-Related Marketing on The Brand Preference of Gen Z to Clothing Brands in Metro Manila - Feliciano, Kyla Marie; David, Madeline Iryle; Gutierrez, Elyssa; Miguel, Leona Anne; Bandojo, Agnes Jocelyn; Etrata, Jr., Antonio (International Business Education Journal, 2025)
This research looks into the effect of cause-related marketing (CRM) towards the clothing brands that Generation Z chooses in Metro Manila. One of the specific goals is to find out the effect of donation proximity, type of cause, type of support, and length of support on people's choices of clothing brands. With the help of a quantitative descriptive correlational design and purposive sampling, data were taken from 408 qualified Gen Z respondents in Metro Manila who were between the ages of 18 and 26. The information was gathered using paper and online poll forms through Google Forms that used a 6-point Likert scale. The results were looked at using Partial Least Squares Structural Equation Modeling (PLS-SEM). The convergent validity, construct reliability, and discriminant validity was also utilized in the study to ensure reliable and valid data. The results show that donation proximity, type of cause, and length of support have significant effects on which clothing brands Generation Z likes. However, type of support did not have a significant effect on brand preferences. Type of Cause, Length of Support, and Type of Support all had small effect sizes (f2 = 0.064, f2 = 0.160, and 0.006, respectively). Donation proximity had a medium effect size (f2 = 0.247). The study's conclusion is that local causes, especially those that are close to where the donation is made, have a big effect on Generation Z's good brand preferences in the local clothing industry. People like brands that support causes that help people, animals, the environment, and health. Long-term and consistent participation in CRM activities has a big effect on brand preferences. Based on the results, clothing brands in Metro Manila should support local causes, stick to well-known problems, and offer consistent, long-term support to effectively engage Generation Z customers.